De-stiffening drug therapy and blood pressure control - Michel E Safar (Dove Medical Press, 2010)
Michel E SafarParis-Descartes University, Faculty of Medicine, Hôtel-Dieu Hospital, AP-HP, Diagnosis Center, Paris, FranceAbstract: In hypertensive subjects, cardiovascular risk reduction is critically related to the decrease of systolic blood pressure (SBP). De-stiffening therapy means that, in a controlled therapeutic trial of long duration, a selective reduction of SBP has been obtained in the studied group by comparison with the control group, and that this SBP reduction is due to a decrease of either arterial stiffness, or wave reflections, or both. Central SBP reduction and cardiovascular remodeling are specifically involved. Most protocols require the presence of an angiotensin II blocker, potentially associated with a diuretic compound and/or a calcium-channel blocker. Cardiovascular outcomes are significantly reduced by comparison with the control group, particularly when this latter group involves administration of a betablocking agent.Keywords: hypertension, pulse pressure, large arteries, de-stiffening drug therapy